Implementation of Independent and Group Muroja'h Methods to Improve Qur'an Memorization - Al Hilal Hamdi; Amini, Amini (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
Among the problems faced by Qur'an memorizers is the ability to memorize quickly, but memorization is often weak or difficult to maintain due to the lack of precise methods that are adapted to the character of the students. This study aims to analyze and describe the process of implementing the independent and group muroja'ah method to improve the memorization of the Qur'an at the Tahfidz House of Ma'had Abu Ubaidah bin Al-Jarrah Medan. The descriptive qualitative method is used through in-depth interviews, observations, and document studies, with interactive data analysis through reduction, presentation, and conclusion drawn. The results showed that independent muroja'ah fostered independence, discipline, and self-correction skills, effective for long-term memorization retention, while group muroja'ah increased social motivation, tajweed accuracy, and letter makhraj through direct tasmi'. The muroja'ah group excelled in the quality of reading, while the independent muroja'ah was better in the quantity and consistency of the daily. This study concludes that the optimal improvement in memorization is obtained through the integration of the two methods according to the character and phase of student development.